Resources and Resilience: An Assets Based Examination of Native Student Success - Diane Hirshberg; Diane Erickson (Adult Education Research Conference, 2007)
Alaska Native alumni of the University of Alaska Anchorage, graduating between 1975 and 2005, were interviewed to explore the key events, relationships, and activities from pre-K through higher education that influenced their decision to attend college and complete a baccalaureate degree.